(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2025)
This research examines the correlation between financial inclusion and financial technology (fintech), particularly emphasizing how fintech can expedite the digital financial transformation in Algeria. This research examines how individuals and institutions are able to access financial products and services, contributing to broader economic development. The study covers the period from 2016 to 2022, employing a descriptive-analytical methodology and incorporating the deductive method for analyzing economic data derived from official statistics and World Bank reports. According to the World Bank data, the adoption of fintech is slowing down due to the deficiency in financial knowledge of the Algerian banking system. According to World Bank data, the results indicate that Algeria is making slow progress in implementing fintech solutions to enhance financial inclusion. This stagnation is attributed to low financial literacy levels and the underdeveloped banking system. The originality of this paper lies in its focus on the intersection between fintech adoption and financial inclusion in the Algerian context, a relatively underexplored area. The study affirms the need to accelerate the digitization of financial and banking services in Algeria by promoting fintech products, improving software infrastructure, and enhancing network readiness indicators. The research concludes with recommendations for policymakers to improve digital financial literacy and foster innovation in banking technologies to achieve broader financial inclusion.